Omega-Psir: From the repository to the research knowledge base experience of Warsaw University of Technology - Henryk Rybiński; Jakub Koperwas; Łukasz Skonieczny; Marek Kozłowski; Wacław Struk (Foundations of Management, 2013)
This paper is devoted to a solution for building a research knowledge base for the university. An experience in developing a specialised software for building such a knowledge base is presented. We present the functionality of the system, as well as, sketch applied AI technologies aiming at providing features attractive for the system beneficiaries. It is shown that although a classical repository is the main part of the system, the essential value of the solution is in providing analytical tools for the 'research management'. First lessons learned from deploying the software at Warsaw University of Technology are also discussed. The platform has been developed under the SYNAT project, aimed at building nation-wide scientific information infrastructure
Keywords: 650; digital library; knowledge base; scientific resources; repository